STATISTICAL ANALYSIS OF RESULTS A STAND EXPERIMENTAL RESEARCHES OF CHANGE OF AXIAL FORCE AT THE BORING DRILLING BY A CHISEL ІІІ 93С - Мойсишин, Василь Михайлович; Лисканич, Ольга Михайлівна; Масьовський, Андрій Ігорович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
s a result of stand experimental researches of change of axial force at the boring drilling by a chisel ІІІ 93С, that the instantaneous values of the axial loading answer the normal law of distributing, and the explored casual process is stationary and ergodic. It enables during the analysis of underlying structure of dynamic constituent of force to use only one realization of record of change of axial effort on mining hole.